Insights into the aetiologies of hypercementosis: A systematic review and a scoring system. (February 2023) - Massé, Léa; Garot, Elsa; Maureille, Bruno; Le Cabec, Adeline
Abstract: Objectives: This paper aims to better define hypercementosis, investigate its described potential aetiologies, and determine whether there are different patterns of cementum apposition and if they are a function of their supposed aetiology. Design: A literature review was undertaken using the Medline, DOSS, Scopus and Cochrane Library electronic databases. Two co-authors selected the published works independently, extracted the data in accordance with the PRISMA statement. Results: Among 546 articles, 75 articles were finally selected. Eight different supposed aetiologies were identified: (1) intensive masticatory effort, (2) systemic disease, (3) carious lesion and apical periodontitis, (4) impaction, (5) periodontal disease, (6) concrescence, (7) super-eruption, and (8) drugs. Some of these aetiologies can be combined in the same tooth. Hypercementosis manifestations are various in nature and extent with different patterns that may be aetiology-specific. To improve the description and associated consistency in the characterisation of hypercementosis, in this review but also in future studies, we propose a new qualitative scoring system to quickly characterise hypercementosis and determine its most relevant aetiology. Conclusions: This systematic review demonstrates that hypercementosis is a complex and not yet well-defined condition. Some forms of apposition are specific to a given aetiology. The hypercementosis characterisation may contribute to document the oral condition and/or the individuals masticatory activity. Highlights: Hypercementosis: complex and not yet well-defined aetiologies and manifestations. Eight aetiologies identified in this systematic review. A new scoring system is proposed to describe qualitatively hypercementosis. Patterns of cementum apposition are distinguished depending on different aetiologies.